Islamic Education Based On Integration Of Science - Sholehah, Nur Rahmadhani (Halaqa: Journal of Islamic Education, 2025)
This paper examines Islamic education based on the integration of knowledge with the aim of connecting or relating general science or science to religious science and vice versa. This research method uses a qualitative method with a library research approach, which is a research approach by researching research through various literatures, books or journals that are relevant to data analysis discussions with data condensation, data presentation, and verification of conclusion drawn. The results of this study show that Islamic education based on the integration of science and science aims to unite Islamic values with modern science in harmony. The ideas of Amin Abdullah and Imam Suprayogo emphasized the importance of the connection between sciences based on the Qur'an and Hadith. However, its implementation still faces challenges such as the dichotomy of knowledge, weak curriculum, and technological limitations. This study recommends strengthening human resources, an integrated curriculum, and interdisciplinary policies. The implication is that regulations and teacher training are needed to support contextual integration. Follow-up research is suggested to explore the long-term impact on learners' character, the role of society, and best practices between educational institutions.